STRATEGI BADAN USAHA MILIK DESA (BUMDES) AMANAH DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA SINDUHARJO - MAS'UDI; Mei Maemunah (Halu Oleo University, 2025)
This study aims to analyse the strategies of the Amanah Village-Owned Enterprise (BUMDes) in improving the welfare of the community in Sinduharjo Village by using the strategic management theory proposed by Wheelen and Hunger. This theory emphasises the strategic management process, which includes environmental analysis (internal and external), strategy formulation, implementation, as well as evaluation and control. The research employs a qualitative method with a case study approach. The findings indicate that BUMDes Amanah actively conducts SWOT analysis to identify strengths, weaknesses, opportunities, and threats in managing its business units, such as microfinance, multipurpose hall rental, and playground operations. The formulated strategies include strengthening institutional capacity, improving service quality, and diversifying businesses based on local potential. Strategy implementation is carried out through increased community participation, collaboration with third parties, and transparent financial management. Regular evaluations are also conducted to adjust work programs in line with community needs and conditions. The study concludes that the application of strategy based on Wheelen and Hunger's theory enhances operational efficiency and strengthens BUMDes’ contribution to the social welfare of the Sinduharjo Village community.